Perubahan profil jaringan tulang dan lunak muka serta progresivitas maloklusi kelas III dengan perawatan teknik begg setelah tahap I = Changes in Facial Bone and Soft Tissue Profile and Progressivitas class III .Malo ... - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1991)
The purpose of this study was to evaluate whether the changes in point A, B, Po of the facial bone tissue and inclination of incisors were followed by its corresponding overlying soft tissue profile of the face in class III malocclusions with anterior cross bite at the end of stage 1 of the Begg technique treatment, and to know' whether the progreaaivity of class III malocclusions was hindered at stage 3 of the Begg technique treatment. The criteria of the subject were based on class III dental malocclusions with anterior cross bite, permanent dentition, and treated by the Begg technique. Lateral cephalometric radiographic were taken before treatment, at the end of stage 1 and at stage 3 of Begg technique. Perpendicular lines were drawn from sella, point A, superior labial sulcus (A), point B, inferior labial sulcus a t1) and tip of upper incisor (E), upper lip membrane (C), tip of lower incisor (F), lower lip membrane (D), point P and skin pogonion (Po1) to the Frankfort horizontal plane. Anguler measurements were done by using Downs and Steiner analyzis. The data were compared one among another within each subject The result of the above treatment can be summarized as follows: a. At the end of stage 1 showed that in class III malocclusions with anterior cross bite the change in point A, B, Po of facial bone tissue were followed by its corresponding overlying soft tissue profile of the face. b. At stage 3 showed that in class III malocclusions with anterior cross bite the progressivity of class III malocclusions was hidered.